Location of the dipteran specificity region in a lepidopteran-dipteran crystal protein from Bacillus thuringiensis. - Widner, W R (1990)
Two highly related crystal protein genes from Bacillus thuringiensis subsp. kurstaki HD-1, designated cryIIA and cryIIB (previously named cryB1 and cryB2, respectively), were used to study host range specificity. Their respective gene products are 87% identical but exhibit different toxicity spectra; CryIIA is toxic to both mosquito and tobacco hornworm larvae, whereas CryIIB is toxic only to the latter. Hybrids of the cryIIA and cryIIB genes were generated, and their resultant gene products were assayed for toxicity. A short segment of CryIIA corresponding to residues 307 through 382 was shown to be sufficient for altering host range specificity-i.e., when this region replaced the corresponding segment of CryIIB, the resulting hybrid protein acquired toxicity against mosquitoes. The CryIIA and CryIIB polypeptides differ by only 18 amino acids in this region, indicating that very few amino acid changes can have a substantial effect on the toxicity spectra of these proteins.